THE INFLUENCE OF CAPITAL STRUCTURE AND FIRM SIZE ON PROFITABILITY AND DIVIDEND POLICY (An Empirical Study at Property and Real Estate Sector Listed in Indonesia Stock Exchange during the periods of 2009-2012) - Khoiro, Evada El Ummah; Suhadak, Suhadak; Handayani, Siti Ragil (Profit: Jurnal Adminsitrasi Bisnis, 2016)
The study conducted to enhance the knowledge about capital structure, firm size, profitability, and dividend policy. The study conducted at property and real estate sector listed in Indonesia Stock Exchange (IDX) during the periods of 2009-2012. Data were collected from 36 annual financial statements using purposive sampling. The result shows that Capital Structure has a negative significant influence on Profitability and Firm Size has positive but not significant influence on Profitability. Besides, higher or lower Capital Structure has no influence on Dividend Policy. The study also shows that Firm Size is significant positively influence Dividend Policy. Lastly, Profitability has a positive and significant relationship to Dividend Policy of property and real estate companies listed on IDX.  The study is aim to provide a good suggestion for the management company and investor in Indonesia, even more to contribute to the finance research development, especially in Capital Structure, Firm Size, Profitability, and Dividend Policy.